Physical Properties and Chemical Kinetics for the Interaction of Albumin with Amoxicillin - M. Al-Rufaie, Elham; AL-Zahra, Alaa A. (Iraqi Journal of Science, 2023)
Albumin is the most abundant protein in blood plasma, serves as a circulating depot for endogenous and exogenous (e.g. drugs) compounds due to its ligand binding properties, this work aim to get information about the binding of Amoxicillin (antibiotics) with albumin, and the influence of the solvent polarity and ionic strength on it by using UV -vis spectrophotometric measurements in phosphate buffer of pH7.4 and three different temperature (290, 300, 310) K. The UV absorption shows a change and a shift in the absorbency and a shift in albumin and amoxicillin peaks, the two changes are indicative of complex formation. The stoichiometry of the interaction were calculated by the method of continuous variations which was1:1at pH 7.4.The equilibrium constant was calculated at three different temperature and ΔG°, ΔH° and ΔS° also calculated. The kinetic studies for this interaction follows first order equation with rate constant value of 16×10-4 min-1.